Evaluating the Role of Community Awareness and Screening Programs in Reducing the Breast Cancer Mortality Rates in Nepal - Thapaliya, Sushila Giri (BARUN Journal, 2025)
Breast cancer is a leading cause of cancer-related deaths among women worldwide, including in Nepal. Early detection through community awareness and screening programs significantly reduces mortality rates. However, despite increasing awareness, breast cancer screening remains low in Nepal due to cultural, social, and economic barriers. This study evaluates the effectiveness of community awareness and screening programs in Nepal, focusing on their role in early detection, prevention, and treatment outcomes. Understanding the impact of these programs helps identify gaps in awareness, accessibility, and implementation, ultimately informing policies to improve breast cancer detection and survival rates, especially in under-served areas. The study reviews existing community-based initiatives, including public health campaigns and mobile screening programs. It assesses awareness levels, access to screening services, and challenges faced in their implementation. The analysis considers both urban and rural perspectives to highlight disparities in healthcare access. findings indicate that while awareness has improved in urban areas, rural populations continue to face significant barriers, including stigma, inadequate healthcare infrastructure, and financial constraints. Limited government support and resource availability further hinder effective screening efforts. Community awareness and screening programs play a crucial role in reducing breast cancer mortality. To enhance their effectiveness, targeted, culturally sensitive outreach programs, improved healthcare infrastructure, and stronger government support are necessary, particularly for rural and under-served populations in Nepal.